Formulasi masker gel peel-off “ELCI” (Eleutherine palmifolia dan Citrus reticulata) sebagai antioksidan - Kumalasari, Eka; Prihandiwati, Erna; Nafisa Berliana, Siti; Marta Fransiska, Revita (Jurnal Insan Farmasi Indonesia, 2024)
UV radiation can cause skin damage, including premature aging. Preventing premature aging can be accomplished by the use of cosmetic goods, such as a peel-off gel mask. ELCI is a unique peel-off gel mask with Dayak leek extract (Eleutherine palmifolia) and orange peel extract (Citrus reticulata). These two active compounds have extremely high antioxidant activity. Antioxidants can help prevent aging by reducing ROS generation. The goal of the study is to find the best ELCI peel-off gel mask recipe thatmeets the standards and provides the most synergistic advantages achievable. ELCI is derived from oven-dried plants and extracted utilizing a maceration procedure with 70% ethanol as the solvent. ELCI was divided into three formulae with varying extract compositions for laboratory testing of the preparation's physical qualities. The study found that all ELCI peel-off gel mask compositions passed the physical characteristics test, which included organoleptic, homogeneity, adhesive power, spreadability, pH, dry time, and viscosity. All formulations remained stable during storage after undergoing a 6-cycle cycling test was not significantly different (p>0,05).